Development of E-Flash Cards to Stimulate the Literacy Skills of Group B Children - Octarina Mayang Sari; Riyanto Riyanto; Didik Suryadi (JENTIK : Jurnal Pendidikan Teknologi Informasi dan Komunikasi, 2024)
The study aims to describe the feasibility of E-Flash Card learning media as a medium learning to stimulate the literacy ability of group B children and describe the effectiveness of E-Flash Card media in stimulating capabilities child literacy group B. The study method used is the Research and Development (R & D). The results of this study obtained an average pre-test score of 37.22 and an average post-test score of 80.55, indicating that the development of E-Flash Cards can be an effective method to stimulate the literacy skills of group B children. The E-Flash Card media is said to be feasible based on validation from media experts, material experts, and teacher responses. Validation from media experts obtained 100% Eligibility Percentage, Validation from Material Experts Obtaining a Percentage 100% eligibility, and responses from teachers obtain a percentage of eligibility 100%.